Functional Genomic Validation of the Roles of Soluble Starch Synthase IIa in Japonica Rice Endosperm - Jr., Vito M. Butardo; Luo, Jixun; Li, Zhongyi; Gidley, Michael J.; Bird, Anthony R.; Tetlow, Ian J.; Fitzgerald, Melissa; Jobling, Stephen A.; Rahman, Sadequr (Frontiers in Genetics, 2020)
The enzyme starch synthase IIa (SSIIa) in cereals has catalytic and regulatory roles during the synthesis of amylopectin that influence the functional properties of the grain. Rice endosperm SSIIa is more active in indica accessions compared to japonica lines due to functional SNP variations in the coding region of the structural gene. In this study, downregulating the expression of japonica-type SSIIa in Nipponbare endosperm resulted in either shrunken or opaque grains with elevated proportion of A-type starch granules. Shrunken seeds had severely reduced starch content and could not be maintained in succeeding generations. In comparison, the opaque grain morphology was the result of weaker down-regulation of SSIIa which led to an elevated proportion of short-chain amylopectin (DP 6-12) and a concomitant reduction in the proportion of medium chain amylopectin (DP 13-36). The peak gelatinisation temperature of starch and the estimated glycaemic score of cooked grain as measured by starch hydrolysis index were significantly reduced. These results highlight the important role of medium-chain amylopectin in influencing the functional properties of rice grains, including its digestibility. The structural, regulatory and nutritional implications of down-regulated japonica-type SSIIa in rice endosperm are discussed.